Prenatal cocaine exposure disrupts the dopaminergic system and its postnatal responses to cocaine. (13th December 2017) - Riley, E.; Maymi, V.; Pawlyszyn, S.; Yu, L.; Zhdanova, I. V.
Abstract : Impaired attention is the hallmark consequence of prenatal cocaine exposure (PCE), affecting brain development, learning, memory and social adaptation starting at an early age. To date, little is known about the brain structures and neurochemical processes involved in this effect. Through focusing on the visual system and employing zebrafish as a model, we show that PCE reduces expression of dopamine receptor Drd1, with levels reduced in the optic tectum and other brain regions, but not the telencephalon. Organism‐wide, PCE results in a 1.7‐fold reduction in the expression of the dopamine transporter ( dat ), at baseline. Acute cocaine administration leads to a 2‐fold reduction in dat in drug‐naive larvae but not PCE fish. PCE sensitizes animals to an anxiogenic‐like behavioral effect of acute cocaine, bottom‐dwelling, while loss of DAT due to genetic knockout (DATKO) leads to bottom‐dwelling behavior at baseline. Neuronal calcium responses to visual stimuli in both PCE and DATKO fish show tolerance to acute cocaine in the principal regions of visual attention, the telencephalon and optic tectum. The zebrafish model can provide a sensitive assay by which to elucidate the molecular mechanisms and brain region‐specific consequences of PCE, and facilitate the search for effective therapeutic solutions. Abstract : Neuronal responses to visual stimuli are no longer modified by cocaine in dopamine transporter knockout zebrafish.